Influence of leaf and base lesion of herbaceous cutting in the guava rooting of the selection 8501-9 - Santoro, Patricia Helena; Mikami, Adriana Yatie; Souza, Silvia Graciele Hülse de; Roberto, Sérgio Ruffo (Semina: Ciências Agrárias, 2010)
With the objective of evaluate the potential of rooting of the selection of guava tree 8501-9 were using herbaceous cutting with 10-12 cm of length in two make of the prepared (simple cut without lesions and cambium exposition), and three suppression intensity of the leaves (without leaves, with half leaves and intact leaves). The experimental design was completely randomized with five repetitions in factorial arrangement 2 x 3, with ten cutting for parcel. After the preparation with IBA the cutting had been placed to rooting in plastic box (44 x 30 x 7 cm) with carbonized rice hulls, in camera of nebulization. After 78 days, evaluated the leaf retention, survive of the cutting, the number of cutting roots and of roots, the length and fresh and dry mass of the roots. The interaction between lesions and presence of leaves was not significant, indicating like this factors act in independent form in relation the study factors. The leaves suppression resulted in cutting death. The cambium exposition not proportion vantage on root cutting herbaceous. For the gotten results it was observed that the interaction between lesion and leaf presence was not significant, indicating that these factors act of independent form in relation to the evaluated parameters. Cutting with base lesion presented addition of only 10% of foliar retention and percentage of roots cutting. Cutting with a pair of leaves had been superior to the parameters of the mass fresh and dry of root in relation to the cutting with half leaves, and the cutting without leaves not presented formation of roots being presence of leaves fundamental to roots promotion.